2003
DOI: 10.1063/1.1570172
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Microwave Detection of Corrosion Precursor Pitting under Thin Dielectric Coatings in Metallic Substrate

Abstract: Detection of corrosion precursor pitting on metallic surfaces under various coatings and on bare metal is of keen interest in evaluation of aircraft fuselage. Near-field microwave nondestructive testing methods, utilizing open-ended rectangular waveguides and coaxial probes, have been used extensively for detection of surface flaws in metals, both on bare metal and under a dielectric coating. This paper presents the preliminary results of using microwave techniques to detect corrosion precursor pitting under p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…With the decrease in aperture dimensions and maintaining a low frequency, Hugues et al demonstrated an increased special resolution on aluminum substrates. 182,184 Kharkovsky et al, 185 using focused and synthetic imaging techniques, focused on three recent applications of microwave and millimeter-wave NDT to detect disbonding between carbon fibre within a concrete structure, corrosion detection on aluminum and steel substrates as well as the flaws in insulation foam.…”
Section: Microwave and Millimeter-wave Ndtmentioning
confidence: 99%
See 3 more Smart Citations
“…With the decrease in aperture dimensions and maintaining a low frequency, Hugues et al demonstrated an increased special resolution on aluminum substrates. 182,184 Kharkovsky et al, 185 using focused and synthetic imaging techniques, focused on three recent applications of microwave and millimeter-wave NDT to detect disbonding between carbon fibre within a concrete structure, corrosion detection on aluminum and steel substrates as well as the flaws in insulation foam.…”
Section: Microwave and Millimeter-wave Ndtmentioning
confidence: 99%
“…Hugues et al 182 demonstrated the detection of defects using Ka-Band (26.5–40 GHz) with V-band (50–75 GHz). His work also compared the effect of changing the bandwidth from Ka-Band to U-Band (40–60 GHz) and from V-Band to W-band (75–110 GHz).…”
Section: Corrosion Monitoring and Detectionmentioning
confidence: 99%
See 2 more Smart Citations